2020
DOI: 10.1002/pi.6082
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and optical properties of novel brilliant cresyl blue dye‐doped poly(methyl methacrylate) as selective cut‐off laser filters

Abstract: Dye doped polymer films of poly(methyl methacrylate) (PMMA) and brilliant cresyl blue (BCB) dye were synthesized using the solution casting technique. This work aims to investigate the influence of BCB dye doping on the structural, optical, dielectric and mechanical properties of PMMA. XRD reveals an increase in PMMA amorphicity with BCB loading. This suggests the solubility of BCB dye within PMMA. Fourier transform IR confirms the interaction between BCB dye and PMMA. The transmittance T of PMMA decreases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…Firstly, it should be mentioned that the tensile test is considered an efficient and heavily used mechanical test in the case of polymeric systems 61–64 . This test helps in finding important parameters.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Firstly, it should be mentioned that the tensile test is considered an efficient and heavily used mechanical test in the case of polymeric systems 61–64 . This test helps in finding important parameters.…”
Section: Resultsmentioning
confidence: 99%
“…For example, at 2 wt.% PbO, these values are 1988 MPa, 56.5 MPa, and 6.9%, respectively. Knowing that pure PVC has a tensile strength of 48.4 MPa 66 and pure PMMA has a tensile strength of 16.26 MPa 63 . In detail, the improvement in E with loading could be due to the better distribution of the PbO NPs within the blend film, which limits the mobility (motion) of the polymer chains (as seen in SEM images).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…44 Another two recent studies investigated polymer/dye blends featuring PMMA (Figure 2). In the first study, El-Gamal et al 45 prepared brilliant cresyl blue dye (BCB)-doped PMMA films with different concentrations of BCB, ranging from 0.2 to 2 wt%, by solution casting. They revealed that BCB is soluble in the PMMA matrix; however, the introduction of 2 wt% BCB reduces the crystallinity of PMMA from 32 to 11.9%.…”
Section: Effect Of the Concentration Of The Dyementioning
confidence: 99%